Potensi Antiadhesi Senyawa Aktif Hibiscus sabdariffa L Pada Penghambatan Protein Target IcsA Shigella flexneri Melalui Studi in Silico Molecular Docking - Rizky Fajar Imam Asshiddiq; Arif Yahya; Rio Risandiansyah (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2021)
Introduction: Diarrhea in Indonesia is a disease with a high prevalence, one of which is caused by S. flexneri infection through exposure, adhesion, invasion and colonization process. H. sabdariffa L is one of the herbs that has anti-adhesion potential, however, the anti-adhesion potential of this herb against S. flexneri is still unknown. The adhesion of S. flexneri to host cells is mediated by IcsA, so this study was conducted to determine whether H. sabdariffa L could bind to the target protein IcsA S. flexneri.Methods: This study used the In silico molecular docking method by tethering the 3D structure of 25 active compounds from H. sabdariffa L obtained from Pubchem, and target protein IcsA S. flexneri (5KE1) obtained from RCSB using a docking server with Ciprofloxacine as control.Results: H. sabdariffa L compound has better affinity than Ciprofloxacine. The five compounds with the best free bond energy values are Quercetin-3-rutinoside (-9.21 kcal/mol), Leucoside (kaempferol-3-O-sambioside) (-8.83 kcal/mol), Quercetine-3-glucoside (-8.23 kcal/mol), Tiliroside (-7.86 kcal/mol), Caffeoylquinic acid isomer (Isochlorogenic acid (-7.43 kcal/mol), the value of the inhibition constanta is 178.61 nM, 337.61 nM, 924.29 nM, 1.15 uM, dan 1.69 uM, the value of the surface interactions is 525.416 Å, 751.689 Å, 564.99 Å, 803.103 Å, 572.111 Å, and the number of amino acid residues is 3,9,5,9,8.Conclusion: Quercetine-3-rutinoside, Leucoside (kaempferol-3-O-sambioside), Quercetine-3-glucoside, Tiliroside, Caffeoylquinic acid isomer (Isochlorogenic) can bind to S. flexneri and has the potential to be used as an anti-adhesion.Keywords: Antiadhesion, Hibiscus sabdariffa, Shigella flexneri, Fluoroquinolone ciprofloxacine, in silico.